Meta-Analysis: Correlations between Knowledge, Self-Efficacy, and Social Support on HIV testing in Homosexual - Karismatika Surya Gumilar; Argyo Demartoto; Bhisma Murti (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: HIV is an infectious disease for which there is no cure. Homosexuals are a vulnerable group for HIV transmission. One of the HIV-AIDS control programs is to make HIV testing a standard of service in all health facilities. This study aims to analyze the influence of self-efficacy, social support, and knowledge in carrying out HIV tests on homosexuals. Subjects and Method: This study is a systematic and meta-analysis study, with PICO as follows: Population= Homosexual. Intervention= Good knowledge, high self-efficacy, and high social support. Comparison= Poor knowledge, low self-efficacy, and low social support. Outcome= Use of HIV Testing. The articles used in this research were obtained from several databases including PubMed, Google Scholar and Scopus. These articles were collected over 2 weeks. The keywords to search for articles are as follows: